(untitled) (Journal of the College of Basic Education, 2023)
The research was conducted to find out the effects of dexamethasone in different doses on blood and biochemical parameters and body weight on male mice for a period of one month. In this research, (60) adult Swiss rats of the Balbstrain were used, their weights ranged between 25-30 gm, at the age of 12 weeks, then they were divided into Three equal groups.The first group, the control group, was injected with 0.1 ml of physiological saline at a concentration of 0.9 mg/kg. As for the second and third groups, they were injected with 0.1 ml of an aqueous solution containing 0.2 and 0.8 mg / kg of dexamethasone sodium phosphate as therapeutic and highly concentrated doses, respectively, as the injection continued every 48 hours for a month.Body weight was recorded weekly, and blood tests were conducted, total count of red blood cells, total count of white blood cells, estimation of the size of packed blood cells, measurement of the amount of hemoglobin, conducting biochemical tests on blood serum, measuring the level of total protein, estimating the level of cholesterol and estimating the level of glucose.The results of the study showed a significant decrease p < 0.05 in the average body weight of the animals treated with the dose of 0.8 mg / kg compared to both the group treated with the dose of 0.2 mg / kg and the control group, while the results of blood tests indicated a significant increase in the number of red blood cells, hemoglobin and blood cells CFL and a decrease in white blood cells in the third group. A significant decrease was observed in the total cholesterol concentration of the 0.8 mg/kg treatment group, compared with the 0.2 mg/kg treated animals and the control group. Treatment with dexamethasone also led to a significant increase p<0.05 in the glucose concentration of the treated group by 0.2 and 0.8 mg/kg, respectively. Compared to the control group, while the total serum protein concentration did not record any significant difference (P < 0.05).